Anatase Mg0.05Ta0.95O1.15N0.85: a novel photocatalyst for solar hydrogen production. Issue 89 (9th September 2016) - Gao, Honglin; Zhao, Meiming; Yan, Shicheng; Zhou, Peng; Li, Zeyan; Zou, Zhigang; Liu, Qingju
Abstract : Anatase Mg0.05 Ta0.95 O1.15 N0.85, exhibiting a narrow band gap for solar hydrogen, is a promising visible-light-response photocatalyst for photocatalytic or photoelectrochemical water splitting. Abstract : Anatase Mg0.05 Ta0.95 O1.15 N0.85, exhibiting a narrow band gap for solar hydrogen, is a promising visible-light-response photocatalyst for photocatalytic or photoelectrochemical water splitting. The excellent photocatalytic activity can be attributed to the satisfying light absorption and electron–hole separation rate.